Respuesta :
3(x+1)=5(x-2)+7
First: you would distribute your number's
You will get: 3x+3=5x-10+7
Next: Combine like terms
You will get: 3x+3= 5x-3
Next: Add your -3 on both sides
You will get: 3x+6=5x
Next: Subtract your 3x on both sides
You will get: 6= 2x
Finally: You will divide each side by 2
Your answer would be: x= 3
HOPE THIS HELPS! ^_^
First: you would distribute your number's
You will get: 3x+3=5x-10+7
Next: Combine like terms
You will get: 3x+3= 5x-3
Next: Add your -3 on both sides
You will get: 3x+6=5x
Next: Subtract your 3x on both sides
You will get: 6= 2x
Finally: You will divide each side by 2
Your answer would be: x= 3
HOPE THIS HELPS! ^_^